PENGARUH BOOK TAX DIFFERENCE, ARUS KAS, TINGKAT HUTANG DAN KINERJA PERUSAHAAN TERHADAP PERSISTENSI LABA (Studi Empiris Pada Perusahaan Manufaktur Yang terdaftar di BEI Tahun 2011-2016) - Itemazatulo Zatulo Lase (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This research was aimed to examine and find out empirical evidence of the influence of book tax difference on earning persistence, to know whether cash flow has a positive effecton earning persistence, to know whether the debt level has a positive effect on earnings persistence,to find out whether the company’s performance has a positive effect on earning persistence. The character of this research by using quantitative research. Quantitative research is the data measured in a numerical scale (number). The population that will be observed in this research is a manufacturing company listed on the Indonesia Stock Exchange in 2011-2016. Data was collected through the financial statement an annual reports of companies. The number of samples in this research has total number 60 samples. the data was collected using purposive sampling method. The analysis of this research was panel regression analysis.The method of anlysis of study using software named SPSS 16. The result showed that 1) Permanent Difference has no effect on Earning Persistence. 2)Temporary differences have no effect on Earning Persistence. 3) Cash Flow Operation has a positive effect on Earning Persistence. 4) Debt level has a positive effect on Earning Persistence.5) Company performance has no effect on Earning Persistence. Keywords : Book tax Difference,Permanent Difference, Book Tax Difference, Cash Flow, Debt Level, Profitability,Earning Persistence